Элементы методологии прогнозирования параметров плитных конструкций подземных частей зданий - Шумаков, И. В.; Секретная, В. Н. (Ways to Improve Construction Efficiency, 2014)
The method of levelness calculation for the buildings is defined. Factors and variables which depend on concrete levelness are described. The example of concrete levelness survey, processing of survey data and calculation is given. The results of the calculation are compared to the standard classification which is developed by American concrete institute. Using the above mentioned method of calculation it is possible to avoid defect of wrong levelness of concrete slab, decrease the duration of construction project, and increase the quality of works. The method of calculation would be useful to consider using appropriate survey and measuring equipment with following mathematic processing.